THE INHIBITORY ACTIVITY OF THE EXTRACTS OF POPULAR MEDICINAL HERBS ON CYP1A2, 2C9, 2C19 AND 3A4 AND THE IMPLICATIONS FOR HERB-DRUG INTERACTION - Fasinu, Pius Sedowhe; Bouic, Patrick J; Rosenkranz, Bernd (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Studies have suggested an increasing practice of concurrent herb-drug consumption. One of the major clinical risks of such concomitant herb-drug use is pharmacokinetic herb-drug interaction (HDI). This is brought about by the ability of phytochemicals to inhibit or induce the activity of metabolic enzymes. The aim of this study was to investigate the potential of the crude aqueous extracts of three popular medicinal herbs used in South Africa to inhibit major cytochrome P450 (CYP) enzymes. Materials and Methods: The extracts of Bowiea volubilis, Spirostachys africana and Tulbaghia violacea were incubated with human liver microsomes (HLM) to monitor the phenacetin O-deethylation, diclofenac 4’-hydroxylation, S-mephenytoin 4’-hydroxylation and testosterone 6β-hydroxylation as respective probe reactions for CYP1A2, CYP2C9, CYP2C19 and CYP3A4. The inhibitory activity, where observed, was profiled against the extract concentration. Results: Extracts of Bowiea volubilis inhibited the metabolic activity of CYP1A2 and CYP3A4 with IC50 values of 92.3 ± 5.5 g/mL and 8.1 ± 0.6 g/mL respectively. Similar observation with Spirostachys africana showed inhibitory activity against CYP1A2 and CYP3A4 with respective IC50 values of 14.3 ± 0.6 g/mL and 47.4 ± 2.4 g/mL. Tulbaghia violacea demonstrated relatively weak inhibitory activity against CYP1A2 (767.4 ± 10.8 g/mL) and CYP2C9 (921 ± 15.3 g/mL). Conclusion: The results suggest the potential for HDI between the herbs and the substrates of the affected enzymes, if sufficient in vivo concentration is attained.